The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.chest.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Disease vs Urinary Antigen-Confirmed Pneumococcal Community-Acquired Pneumonia

Abstract: A high percentage of confirmed pneumococcal pneumonia is diagnosed by UAT. Despite differences in clinical characteristics and outcomes, IPP is not an independent risk factor for 30-day mortality compared with NIPP, reinforcing the importance of NIPP for pneumococcal pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Previous studies have shown low serum albumin or high serum CRP concentrations to be risk factors for bacteremia in patients with CAP [ 15 , 20 , 21 , 29 ]; our findings are consistent with this. Low serum albumin concentration is a risk factor for and a predictor of morbidity and mortality, regardless of the disease [ 30 ], and a relationship exists between hypoalbuminemia and severe infection due to the elevation of cytokine levels during systemic inflammation [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown low serum albumin or high serum CRP concentrations to be risk factors for bacteremia in patients with CAP [ 15 , 20 , 21 , 29 ]; our findings are consistent with this. Low serum albumin concentration is a risk factor for and a predictor of morbidity and mortality, regardless of the disease [ 30 ], and a relationship exists between hypoalbuminemia and severe infection due to the elevation of cytokine levels during systemic inflammation [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…34 Moreover, the most common cause of bacteremic pneumonia was pneumococcus in 74% of patients, and although the authors did not look at CRP levels, patients with invasive pneumococcal CAP usually presented greater levels of CRP. 35 A recent meta-analysis that compared the combination of a b-lactam with a macrolide vs a b-lactam with a fluoroquinolone showed no significant differences in short-term mortality (adjusted risk ratio, 1.26; 95% CI, 0.95-1.67; I 2 , 43%) 36 ; and another metaanalysis showed that ceftriaxone combination therapy was similar in terms of treatment success compared with fluoroquinolone monotherapy in patients with CAP. 37 The study by Postma et al 6 was a cluster-randomized clinical trial that showed that a b-lactam was not inferior to a combination of a b-lactam with a macrolide or a fluoroquinolone alone for patients with nonsevere CAP; however, this study had several methodologic limitations that made the conclusions not generalized…”
Section: Discussionmentioning
confidence: 99%
“…Acute respiratory distress syndrome (ARDS) is a potential complication of severe CAP that is reported in ∼3% of patients hospitalised with pneumococcal CAP [9]. This condition is characterised by the rapid development of severe acute respiratory failure, and is associated with high morbidity and mortality despite advances in supportive care and ventilator management [10,11].…”
Section: Introductionmentioning
confidence: 99%